The Effectiveness Test of Basil Leaf Extract and Bilimbi Fruit in Control of Cocoa Sucting Pests (Helopeltis spp.) - Pasaribu, Apriyeni; Sudirman, Albertus; Utoyo, Bambang (Universitas Sebelas Maret, 2023)
Helopeltis spp. is a major pest of plantation crops, especially on cocoa plants. This pest attacks the fruit and shoots of cocoa plants by sucking the liquid from plant parts which cause fruit rot and reduces production. Control that is often done by farmers is by using synthetic insecticides. The use of synthetic insecticides in controlling pest attacks turns out to have a negative impact on the surrounding environment and even on its users, so we need an alternative that does not have a negative impact such as environmentally friendly vegetable insecticides. There are many plants that have the potential as vegetable insecticides such as basil and starfruit. The purpose of this study was to obtain the best extract from basil leaf extract, star fruit wuluh, and the combination of the two extracts against the mortality of Helopeltis spp. The research was carried out at the Plant Laboratory II, Department of Plantation Cultivation, Lampung State Polytechnic, from November 2020 to February 2021. This research was conducted using a Randomized Block Design with 4 treatments and 6 replications so that there were 24 experimental units. Each experimental unit contained one treatment and 11 Helopeltis spp. This research was finding that the highest mortality at 4 DAA was found in the combination treatment of basil leaf extract and starfruit with a mortality percentage of 33.33%. The highest mortality in this study was 45.45% at 6 DAA treatment with a combination of basil leaf extract and star fruit, meaning that the treatment in this study was considered less effective. This research conclude that the combination of basil leaf extract and star fruit is able to control cocoa fruit-sucking pests (Helopeltis spp.) with a mortality of 45.45%.